Simultaneous removal of polycyclic aromatic hydrocarbon and heavy metals from an artificial clayey soil by enhanced electrokinetic method. (1st July 2018) - Saberi, Nima; Aghababaei, Mohammad; Ostovar, Mojtaba; Mehrnahad, Hamid
Abstract: Contamination of soil by a mixture of organic and non-organic pollutants due to various anthropogenic and natural causes is one of the most important issues in soil pollution. Generating a single layer of soil is a time-consuming process, and soil is a significant part of the environmental cycle; thus, protection and remediation of soil are of paramount importance. In this study, phenanthrene (PHE) as a representative for polycyclic aromatic hydrocarbon and lead (Pb), zinc (Zn), and nickel (Ni) as heavy metal pollutants were used because of their synergistic effects and abundant presence in soil. Soils with three different organic matter levels (OM0, OM1, and OM2) were prepared, spiked with pollutants, placed in electrokinetic cells, and remediated for 15 days. To improve the remediation process and increase the efficacy of pollutant removal, pH control methods and extracting agents were used. Two non-ionic surfactants, Tween 80 and Brij 35, and one chelating agent, EDTA, were utilized for this purpose. A total of nine tests were performed. The soil was divided into five equal sections at the end of each test, and the pH and concentration of pollutants were analyzed. Results indicated that the highest removal percentage of PHE was accomplished by Brij 35 (61%) in OM0. Increasing organic matter resulted in decreasing PHE removal. In this regard, Tween 80 showed enhanced performance. The order of removal of heavy metals was zinc > nickel > lead, and zinc had the highest removal rate of 61%. Graphical abstract: Image 1 Highlights: Extracting agents improved heavy metals and PAH simultaneous remediation efficiency. Increasing organic matter resulted in decreasing phenanthrene (PHE) removal. The order of removal of heavy metals was zinc > nickel > lead. Zinc had the highest removal rate of 61%.